Suppression of Gushing by Hop Constituents - Hanke, Stefan; Kern, Matthias; Herrmann, Markus; Back, Werner; Becker, Thomas; Krottenthaler, Martin (BrewingScience, 2009)
Gushing is one of the most unsolved problems in brewing. This is a very severe quality defect. Efforts are being made to reveal the identity of gushing components. The beer defect of gushing is a temporary brewery problem that is primarily caused by fungi derived factors. In this work the influence of humulones, pure linalool and hop oils on natural occurring gushing and an activated carbon (AC) induced gushing of commercial brews was tested. The experiments proved that linalool significantly reduces the gushing volume. Hop oils (linalool) decreased the gushing tendency of beer. Gushing, induced by activated carbon, is suppressed by the addition of linalool and humulones. These results suggest that some of the properties of the hop constituents, humulones and linalool, prevent beer from gushing especially when hops are added at late stages of wort boiling.